2022
DOI: 10.1038/s41598-022-25224-z
|View full text |Cite
|
Sign up to set email alerts
|

SSTR2 as an anatomical imaging marker and a safety switch to monitor and manage CAR T cell toxicity

Abstract: The ability to image adoptively transferred T cells in the body and to eliminate them to avoid toxicity will be vital for chimeric antigen receptor (CAR) T cell therapy, particularly against solid tumors with higher risk of off-tumor toxicity. Previously, we have demonstrated the utility of somatostatin receptor 2 (SSTR2) for CAR T cell imaging, illustrating the expansion and contraction of CAR T cells in tumor as well as off-tumor expansion. Using intercellular adhesion molecule 1 (ICAM-1)-specific CAR T cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 52 publications
(72 reference statements)
0
6
0
Order By: Relevance
“…Notably, a recent study has gone one step further to investigate the potential of using the SSTR2 reporter as a suicide switch to destroy the CAR T-cells when they generate toxic AEs. In this approach, a maytansine–octreotate conjugate, PEN-221 (Tarveda), was used for imaging and elimination of CAR T-cells when they became toxic ( 200 ). Another interesting study used an engineered antibody against DOTA (1,4,7,10-tetraazacyclododecane-1,4,7,10-tetraacetic acid; DAbR1) for both cell tracking and a potential antibody–drug conjugate ( 201 ).…”
Section: Current Advances In Immuno-pet/-spect Imaging Methods and Th...mentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, a recent study has gone one step further to investigate the potential of using the SSTR2 reporter as a suicide switch to destroy the CAR T-cells when they generate toxic AEs. In this approach, a maytansine–octreotate conjugate, PEN-221 (Tarveda), was used for imaging and elimination of CAR T-cells when they became toxic ( 200 ). Another interesting study used an engineered antibody against DOTA (1,4,7,10-tetraazacyclododecane-1,4,7,10-tetraacetic acid; DAbR1) for both cell tracking and a potential antibody–drug conjugate ( 201 ).…”
Section: Current Advances In Immuno-pet/-spect Imaging Methods and Th...mentioning
confidence: 99%
“…Notably, a recent study has gone one step further to investigate the potential of using the SSTR2 reporter as a suicide switch to destroy the CAR T-cells when they generate toxic AEs. In this approach, a maytansineoctreotate conjugate, PEN-221 (Tarveda), was used for imaging and elimination of CAR T-cells when they became toxic (200). Another interesting study used an engineered antibody against DOTA (1,4,7,10-tetraazacyclododecane-1,4,7,10-tetraacetic acid; DAbR1) for both cell tracking and a potential antibody-drug conjugate While most of these reporter/radiotracer studies are still at the preclinical stages, a successful first-in-human trial tracking CAR T-cells has been reported in the case of a 57-year-old man with grade IV glioblastoma whose autologous CD8 + T-cells were genetically engineered to express the herpes simplex virus type 1 thymidine kinase (HSV1-tk) suicide gene for PET imaging with 9-[4-[ 18 F]fluoro-3-(hydroxymethyl)butyl]guanine ([ 18 F]F-FHBG) (203).…”
Section: Car T-cell Distributionmentioning
confidence: 99%
“…Alternative approach is to use a safety switch to eliminate CAR‐T cells once GvHD symptoms develop. For this purpose, Alcaina et al 62 used the combination of the somatostatin receptor 2 (SSTR2), as a suicide gene, with a specific maytansine‐octreotate conjugate PEN‐221. The results of their research highlight the role of SSTR2 not only in the imaging of CAR‐T cells expansion, but also in their removal, making it a promising dual marker.…”
Section: The Potential Of Personalized Allo‐car‐tmentioning
confidence: 99%
“…An applicable modality is magnetic cell separation (MACS); however, Kath et al 60 Alternative approach is to use a safety switch to eliminate CAR-T cells once GvHD symptoms develop. For this purpose, Alcaina et al 62 used the combination of the somatostatin receptor 2 (SSTR2), as a suicide gene, with a specific maytansine-octreotate conjugate PEN-221.…”
Section: Major Challengesmentioning
confidence: 99%
“…In our previous work, we developed CAR T cells co-expressing SSTR2 to enable positron emission tomography (PET) imaging of CAR T cell distribution in the whole body using 68 Ga-DOTATATE or 18 F-NOTA-Octreotide ( 19 , 20 ). Additionally, we demonstrated the use of SSTR2 as a suicide switch to deliver SSTR2-specific drug conjugates and eliminate unwanted CAR T cells that were causing systemic toxicity ( 21 ). In contrast to killing unwanted CAR T cells, this study investigates the effect of low to intermediate doses of radiation delivered by 177 Lu-DOTATATE to CAR T cells that are largely exhausted and dysfunctional yet proliferating within tumors ( 22 ).…”
Section: Introductionmentioning
confidence: 99%